Is there a Place for Prebiotics in the Management of Neonatal Inguinal Hernia? A Preliminary Study - Ben Dhaou, Mahdi; Zouari, Mohamed; Ammar, Saloua; Bouraoui, Amira; Gassara, Imene; Feki, Ines; Zitouni, Hayet; Jallouli, Mohamed; Masmoudi, Jaweher; Gargouri, Abdellatif; et al. (Journal of Neonatal Surgery, 2016)
The objective of this study was to assess the place of prebiotics in the management of neonatal inguinal hernia. Boys with a diagnosis of unilateral non-complicated inguinal hernia, aged less than 40 days, were prospectively followed from January 2012 to December 2014. Clinical and psychiatric data and outcomes were collected before and after prebiotics (Primalac AC) administration. Ninety-eight patients were included. There were 75 inguinal hernias and 23 inguino-scrotal hernias. Before prebiotics administration 72.2% of infants had abdominal distention and 98% had colic. After prebiotics, abdominal distention and colic regressed in 85.2% and 73.2% of patients, respectively. Hernias disappeared clinically in 66.3% of cases. The factors associated with the disappearance of hernias were the type of the hernia (p<0.001), colic (p<0.001), and abdominal distention (p<0.001). Prebiotics would be a new adjunct in the management of neonatal inguinal hernia. They decrease colic and abdominal distention, which seems helpful to prevent strangulation and probably get spontaneous resolution of small hernias.